2017
DOI: 10.1007/s10551-017-3534-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Awareness, Ethical Judgment and Whistleblowing: A Moderated Mediation Analysis

Abstract: This study aims to examine the ethical decision-making (EDM) model proposed by Schwartz (2015), where we consider the factors of non-rationality and aspects that affect ethical judgments of the auditor to arrive at the decision to blow the whistle. In this paper, we argue that the intention of whistleblowing depends on ethical awareness (EAW) and ethical judgment (EJW) as well as there is a mediationmoderation due to emotion (EMT) and perceived moral intensity (PMI) of auditors. Data was collected using an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 78 publications
2
43
0
2
Order By: Relevance
“…Before running the PLS-MGA, we consider it to test the measurement invariance of composite models (MICOM) using a permutation procedure. We test the measurement invariance to ensure that the specific-group difference of the estimation model does not affect the results for the latent variables in the whole group (Henseler et al, 2016;Latan et al, 2017). From the analysis, it can be concluded that there is no difference variance and average values for both groups (see Table 5), which means there is no invariance problem that will affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Before running the PLS-MGA, we consider it to test the measurement invariance of composite models (MICOM) using a permutation procedure. We test the measurement invariance to ensure that the specific-group difference of the estimation model does not affect the results for the latent variables in the whole group (Henseler et al, 2016;Latan et al, 2017). From the analysis, it can be concluded that there is no difference variance and average values for both groups (see Table 5), which means there is no invariance problem that will affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the use of PLSc necessitates large sample size (at least 100 cases) (Latan and Ghozali, 2015;Latan et al, 2017;Latan et al, 2018). PLS-PM has been used by past similar works for analysis purposes (Al-Shbiel, 2016;Al-Shbiel et al, 2018;Al Shbail et al, 2018a;2018b;Obeid et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, little research has tested these types discretely, instead attempting to find more universal motivations for those who choose to disclose (Dozier & Miceli, 1985; Heumann et al, 2013). According to empirical research, personal and situational ethics, for example, are stronger predictors of the intent to blow the whistle, as opposed to the act of whistleblowing, because threats of retaliation or other consequences may become relevant when individuals face the decision to report wrongdoing (Latan et al, 2017; Mesmer-Magnus & Viswesvaran, 2005). Those with intimate, internal knowledge of wrongdoing are more likely to report that they will blow the whistle than those who are external to an organization; however, they prefer to do so anonymously (Latan et al, 2017).…”
Section: The Whistleblower: a Conceptual Definitionmentioning
confidence: 99%
“…According to empirical research, personal and situational ethics, for example, are stronger predictors of the intent to blow the whistle, as opposed to the act of whistleblowing, because threats of retaliation or other consequences may become relevant when individuals face the decision to report wrongdoing (Latan et al, 2017; Mesmer-Magnus & Viswesvaran, 2005). Those with intimate, internal knowledge of wrongdoing are more likely to report that they will blow the whistle than those who are external to an organization; however, they prefer to do so anonymously (Latan et al, 2017). For external whistleblowing intentions, reported levels of perceived ideals and perceived support from the organization may also be significant predictor variables (Sims & Keenan, 1998).…”
Section: The Whistleblower: a Conceptual Definitionmentioning
confidence: 99%